2015
DOI: 10.1111/1750-3841.13115
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid, Organic Acid, and Sugar Profiles of 3 Dry Bean (Phaseolus vulgaris L.) Varieties

Abstract: In this study, we compared the amino acid, organic acid and sugar profiles of 3 different varieties of dry beans (black bean [BB], dark red bean [DRB], and cranberry bean [CB]). The efficiency of the 2 commonly used extraction solvents (water and methanol:chloroform:water [2.5:1:1, v/v/v/]) for cultivar differentiation based on their metabolic profile was also investigated. The results showed that the BB contained the highest concentration of amino acids followed by DRB and CB samples. Phenylalanine, a precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Moreover, organic acid except for oxalic, were shown to have various benefits for human health such as inhibiting the unwanted microflora and improving the intake of nonheme Fe from vegetarian food (Nawirska‐Olszańska, Biesiada, Sokół‐Łętowska, & Kucharska, 2014). Similarly, malic acid was reported as the abundant organic acid in common bean and seeds (Hassan, Saleh, & AbdElgawad, 2018; John & Luthria, 2015). Therefore, B. aegyptiaca leaves were used for cooking as vegetables like spinach.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, organic acid except for oxalic, were shown to have various benefits for human health such as inhibiting the unwanted microflora and improving the intake of nonheme Fe from vegetarian food (Nawirska‐Olszańska, Biesiada, Sokół‐Łętowska, & Kucharska, 2014). Similarly, malic acid was reported as the abundant organic acid in common bean and seeds (Hassan, Saleh, & AbdElgawad, 2018; John & Luthria, 2015). Therefore, B. aegyptiaca leaves were used for cooking as vegetables like spinach.…”
Section: Discussionmentioning
confidence: 95%
“…The oven temperature program commenced at 80°C for 2 min, followed by 300°C from 2 to 15 min, with a 10°C/min hold, and finally a hold of 3 min, with a transfer line temperature of 250°C. In MS, ionization was at −70 V (electron energy) with a source temperature of 200°C (John & Luthria, ).…”
Section: Methodsmentioning
confidence: 99%
“…In MS, ionization was at 270 V (electron energy) with a source temperature of 2008C (John & Luthria, 2015).…”
Section: Metabolites Extraction and Analysismentioning
confidence: 99%
“…Amino acids content varied among the cultivars, species and different parts of same species are reported previously from several studies. From a recent study it was reported that among the amino acid profiles of 3 different varieties of dry beans i.e., black bean, dark red bean and cranberry bean revealed that the black bean contained the highest concentration of amino acids followed by dark red bean and cranberry samples [21]. Kim et al [22,23], who found that of all the amino acids isolated from Momordica charantia, arginine was present in remarkably high quantities, whereas cysteine and methionine were present at the lowest concentrations.…”
Section: Resultsmentioning
confidence: 99%